On a variational inequality for incompressible non-Newtonian thick flows - Miranda, Fernando (2016)
Publicado em "Recent advances in partial differential equations and applications". Contemporary mathematics series of the American Mathematical Society, vol. 666. ISBN 978-1-4704-1521-1